The Capital Structure Determinants of Indonesia Publicly Listed Firms - Carolina Tandya (iBuss Management, 2015)
In order to compete and survive in the unpredictable economy circumstances, corporation should be able to manage the capital structure. This research aims to investigate the influence of capital structure determinants (profitability, firm size, tangibility, and growth opportunity) towards capital structure decision in 138 Indonesia publicly listed firms from the period of 2009 – 2013 using multiple regression model. This research suggests that profitability, firm size, and growth opportunity statistically have significant influence toward corporate leverage. On the other hand, tangibility does not have significant influence toward capital structure decision. Profitability and firm size indicate negative influence towards corporate leverage that support pecking order theory. While, the negative relationship between growth opportunity and corporate leverage is aligned with static trade off theory and agency cost theory. Keywords: Capital structure, Determinants, Indonesia, Public Listed